32. Corelation between age, scrotal circumference, and testis weight on concentration of spermatozoa in aceh bulls - Zaid Zaid; Dasrul Dasrul; Triva Murtina Lubis (Universitas Syiah Kuala, 2019)
The study examines the relationship between scrotal circumference and weight of testis with spermatozoa concentration aceh cattle at different age levels, as many as 20 samples of bull Aceh. The data collected were analyzed using analysis of variance satua direction. When there berbedaan between treatments, the data were further tested by Duncan multiple test, while to determine the relationship between age, scrotal circumference, weighing testis with spermatozoa concentration used simple regression analysis. Results of analysis of variance (ANOVA) scrotal circumference one way to show that there are significant differences (P 0.05) among all three age groups, as well as the concentration of spermatozoa showed significant differences in each age group. Scrotal circumference was positively related to the weight of the testes with regression coefficient (r) = 0, 945), the value (P 0.05), and the concentration of spermatozoa with regression coefficient (r) = 0, 834, the value (P 0, 05), as well as testes weight was positively related to the concentration of spermatozoa with regrsi coefficient (r) = 0, 831,(P 0.05). It can be concluded, the age effect on scrotal circumference, testis weight and the concentration of spermatozoa Aceh cattle.